KELAYAKAN EKONOMIS POLITIK UANG DALAM PEMILIHAN JABATAN EKSEKUTIF (Proceeding Fakultas Ekonomi, 2003)
Money politic is politicakal behavior which is critized by all public. in fact this activity will still always be done althought it is critized by people, since the doer will economically get their benefit. Money politics therefor is still occur in Indonesia in the process executife election and than to be political custom in Indonesia political culture.